2021
DOI: 10.1210/endocr/bqab116
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Gonadotrope Gene Expression Through Regulatory lncRNAs

Abstract: The world of long non-coding RNAs (lncRNAs) has opened up massive new prospects in understanding the regulation of gene expression. Not only are there seemingly almost infinite numbers of lncRNAs in the mammalian cell, but they have highly diverse mechanisms of action. In the nucleus, some are chromatin-associated, transcribed from transcriptional enhancers (eRNAs) and/or direct changes in the epigenetic landscape with profound effects on gene expression. The pituitary gonadotrope is responsible for activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 180 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…To understand the regulatory mechanism of the follicular–luteal transition, a previous study focused mainly on the microRNA (miRNA)–mRNA interactions in ovarian tissue and revealed that some miRNAs, such as miR-200a, miR-200b, and miR-200c, appeared to be critical regulators of ovarian follicular and luteal development ( 53 , 54 ). However, pituitary hormones (FSH and LH) are required for the transition from the follicle to the corpus luteum, which involves receiving feedback signals from gonadal steroids and activin/inhibin signaling pathways ( 55 , 56 ). In our study, DEGs from the follicular–luteal transition of wild-type ewes were mainly enriched in the G2/M transition of mitotic cell cycle, response to BMP, and Wnt signaling pathway of the GO terms and tight junction, TGF-beta signaling pathway, circadian entrainment, gap junction, and hormone-related signaling pathways of the KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the regulatory mechanism of the follicular–luteal transition, a previous study focused mainly on the microRNA (miRNA)–mRNA interactions in ovarian tissue and revealed that some miRNAs, such as miR-200a, miR-200b, and miR-200c, appeared to be critical regulators of ovarian follicular and luteal development ( 53 , 54 ). However, pituitary hormones (FSH and LH) are required for the transition from the follicle to the corpus luteum, which involves receiving feedback signals from gonadal steroids and activin/inhibin signaling pathways ( 55 , 56 ). In our study, DEGs from the follicular–luteal transition of wild-type ewes were mainly enriched in the G2/M transition of mitotic cell cycle, response to BMP, and Wnt signaling pathway of the GO terms and tight junction, TGF-beta signaling pathway, circadian entrainment, gap junction, and hormone-related signaling pathways of the KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the most intensive research on lncRNAs has focused on the level of ovarian tissue in the HPO axis, but little is known about its role in the hypothalamus and its mechanism of regulating reproductive hormones in goats, and the synergistic action of hypothalamus, pituitary and ovary can promote the moderate development of sexual organs and the formation of gametes ( 19 ). Previous studies have confirmed that the expression levels of certain genes in the hypothalamus directly or indirectly significantly affect reproductive activities such as follicle formation, follicular development and ovulation, while the ovulation rate of goats directly affects the fecundity of goats ( 20 ).…”
Section: Introductionmentioning
confidence: 99%